A efetivação do direito humano fundamental ao meio ambiente cibernético do trabalho - Garcia, Daiene Kelly [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work aims to analyze the existence and the need for effective fundamental human right to a cyber work environment. This right arises in the middle of the specifics of contemporary society, named by Jacques Ellul as technical society, and in the consequences of this reality over the environment, and in the relationship of these differences with the fundamental human rights, particularly the right of labor. Technological innovations, especially information and communication technologies, cause changes to the environment in which the human being is inserted, where it interacts and through where it relates to his fellows, changes that identify the cyber environment as an extent and specificity of the environment itself. Labor relationships migrate to this environment and assume properties that converge to their understanding as a cyber work environment. From the identification of such changes, it is intended to demonstrate the inadequacy of the legal treatment given to fundamental human rights in technical society, which must be analyzed in the focus of the peculiarities of this new model of society and the cyber work environment. In order to recognize the existence of the fundamental human right in half cybernetic work environment, which should be presented as a healthy and balanced environment, it is necessary to consider measures for the enforcement of this right. The realization of other fundamental human rights of the worker and of the human society passes in the recognition of the right to a cyber work environment, allowing us to tailor the application of legal instruments for the protection of workers‟ human rights demands that model of society. Set these assumptions, it is observed that the recognition and enforcement of human rights in technical society, specifically the right to a cyber work environment, permeates a necessary individual and collective awareness about the interference, in society and in human life, of a...

Este trabalho tem por objetivo analisar a existência e a necessidade de efetivação material do direito humano fundamental ao meio ambiente cibernético do trabalho. Tal direito surge no bojo das especificidades da sociedade contemporânea, denominada por Jacques Ellul como sociedade técnica, e dos desdobramentos dessa realidade sobre o ambiente de trabalho, bem como da relação de tais especificidades com os direitos humanos fundamentais, em especial o direito ao trabalho. As inovações tecnológicas, notadamente as tecnologias da informação e da comunicação, provocam alterações no ambiente em que o ser humano está inserido, com o qual interage e por meio do qual se relaciona com seus semelhantes, alterações essas que permitem identificar o meio ambiente cibernético como extensão e especificidade do meio ambiente. As relações de trabalho migram para esse ambiente e assumem características particulares que convergem para a sua compreensão como meio ambiente cibernético do trabalho. A partir da identificação de tais mudanças, pretende-se demonstrar a insuficiência do tratamento jurídico conferido aos direitos humanos fundamentais na sociedade técnica, os quais devem ser analisados à luz das peculiaridades desse novo modelo de sociedade e do meio ambiente cibernético do trabalho. Tendo em vista o reconhecimento da existência do direito humano fundamental ao meio ambiente cibernético do trabalho, que deve apresentar-se como um meio sadio e equilibrado, torna-se necessária a discussão de medidas para a efetivação desse direito. A efetivação dos demais direitos humanos fundamentais do trabalhador e do ser humano na sociedade técnica passa, dessa forma, pelo reconhecimento do direito ao meio ambiente cibernético do trabalho, permitindo a adequação da aplicação dos instrumentos jurídicos de proteção aos direitos humanos do trabalhador às demandas desse modelo de sociedade. Fixadas tais premissas, observa-se...
Keywords: Direito e informática; Direitos humanos; Ambiente de trabalho - Aspectos jurídicos; Sociedade da informação; Tecnologia - Aspectos sociais; Direitos fundamentais; Law